The Relationship Between Stress Levels With The Incidence Of Hypertension In The Elderly At Budi Agung Social Institution, Kupang City - Thamara Novelia Laly; dr. I Made Artawan M.Biomed., Sp.An-TI; dr. Derri Riskiyanti Tallo Manafe M.Sc (Universitas Nusa Cendana, 2025)
Background : Hypertension is called the